Kepemimpinan, Inovasi dan Struktur Birokrasi terhadap Efektivitas Usaha Mikro dan Menengah di Kabupaten Garut - Sultan Yusuf Nugraha; Entin Kartini; Ajeng Mayasari (Journal of Management and Bussines (JOMB), 2023)
This research aims to see the relevance of ethical leadership and the work environment as two main factors that influence employee performance in Baros Village, Central Cimahi, West Java. With 53 sub-district employees as samples, data was collected through a survey by distributing questionnaires online. The research results show that at the Baros District Office, employee performance is influenced by the ethical leadership of the Village Head and a good work environment. This ethical leadership and supportive work environment has been proven to improve employee performance. Keywords: Business Effectiveness, Innovation Leadership, Bureaucratic Structure